An Optimal and Flexible Approach for Drought Quantification Based on Standardised Indices - Sergio M. Vicente‐Serrano; Fergus Reig; Santiago Beguería; Ahmed El‐Kenawy; Fernando Domínguez‐Castro; Magí Franquesa; Luis Gimeno‐Sotelo; María Adell‐Michavilla; Amar Halifa‐Marín; Iván Noguera; Miguel Andres‐Martin; Cesar Azorin‐Molina; et al. (International Journal of Climatology, 2025)
In this study we propose a novel approach to standardising drought indices that offers flexibility tailored to local conditions. This involves employing different probability distributions and the Akaike Information Criterion to identify the most appropriate distribution for each region and variable. Following this approach, our proposed methodology enhances the accuracy and comparability across different spatial and temporal scales, with improved representation of extreme drought events. Nonetheless, despite the increased computational requirements associated with this approach, the advantages are substantial. By enhancing accuracy, comparability and adaptability, it may improve drought monitoring and management practices. Moreover, the methodology provides a versatile framework for standardising a wide range of environmental variables beyond traditional drought indices, and software for calculations is provided ( https://github.com/lcsc/FlexDroughtIndex ). Overall, the findings of this study can advance drought assessments by providing an innovative and flexible methodology that addresses key limitations of current approaches.

Assessment of parametric approaches to calculate the Evaporative Demand Drought Index - Iván Noguera; Sergio M. Vicente‐Serrano; Fernando Domínguez‐Castro; Fergus Reig (International Journal of Climatology, 2022)
The Evaporative Demand Drought Index (EDDI), based on atmospheric evaporative demand, was proposed by Hobbins et al. (2016) to analyse and monitor drought. The EDDI uses a nonparametric approach in which empirically derived probabilities are converted to standardized values. This study evaluates the suitability of eight probability distributions to compute the EDDI at 1‐, 3‐ and 12‐month time scales, in order to provide more robust calculations. The results showed that the Log‐logistic distribution is the best option for generating standardized values over very different climate conditions. Likewise, we contrasted this new parametric methodology to compute EDDI with the original nonparametric formulation. Our findings demonstrate the advantages of adopting a robust parametric approach based on the Log‐logistic distribution for drought analysis, as opposed to the original nonparametric approach. The method proposed in this study enables effective implementation of EDDI in the characterization and monitoring of droughts.

Long‐term variability and trends in meteorological droughts in Western Europe (1851–2018) - Sergio M. Vicente‐Serrano; Fernando Domínguez‐Castro; Conor Murphy; Jamie Hannaford; Fergus Reig; Dhais Peña‐Angulo; Yves Tramblay; Ricardo M. Trigo; Neil Mac Donald; M. Yolanda Luna; Mark Mc Carthy; Gerard Van der Schrier; et al. (International Journal of Climatology, 2021)
We analysed long‐term variability and trends in meteorological droughts across Western Europe using the Standardized Precipitation Index (SPI). Precipitation data from 199 stations spanning the period 1851–2018 were employed, following homogenisation, to derive SPI‐3 and SPI‐12 series for each station, together with indices on drought duration and severity. Results reveal a general absence of statistically significant long‐term trends in the study domain, with the exception of significant trends at some stations, generally covering short periods. The largest decreasing trends in SPI‐3 (i.e., increasing drought conditions) were found for summer in the British and Irish Isles. In general, drought episodes experienced in the last two or three decades have precedents during the last 170·years, emphasizing the importance of long records for assessing change. The main characteristic of drought variability in Western Europe is its strong spatial diversity, with regions exhibiting a homogeneous temporal evolution. Notably, the temporal variability of drought in Western Europe is more dominant than long‐term trends. This suggests that long‐term drought trends cannot be confirmed in Western Europe using precipitation records alone. This study provides a long‐term regional assessment of drought variability in Western Europe, which can contribute to better understanding of regional climate change during the past two centuries.

Recent trends in atmospheric evaporative demand in Southwest Iran: implications for change in drought severity - Mahshid Karimi; Sergio M. Vicente-Serrano; Fergus Reig; Kaka Shahedi; Tayeb Raziei; Mirhassan Miryaghoubzadeh (Theoretical and Applied Climatology, 2020)

Vegetation greening in Spain detected from long term data (1981–2015) - Sergio M. Vicente-Serrano; Natalia Martín-Hernández; Fergus Reig; Cesar Azorin-Molina; Javier Zabalza; Santiago Beguería; Fernando Domínguez-Castro; Ahmed El Kenawy; Marina Peña-Gallardo; Iván Noguera; Mónica García (International Journal of Remote Sensing, 2020)